CONVERGENCE THEOREM IN CAT(0) SPACE - Abkar, A.; Eslamian, M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
Some new iterative process for multivalued mappings in CAT(0) spaces are introduced. Strong and convergence theorems for such iterative process are established.